ANALISIS PENGARUH KEPEMIMPINAN KERJA, MOTIVASI DAN INSENTIF TERHADAP KEPUASAN KERJA PEGAWAI BADAN PENGELOLAAN KEUANGAN PENDAPATAN DAN ASET DAERAH KOTA BINJAI - Ginting, Umrizal; Surya, Alwin; Sembiring, Rasmulia (LPPM Universitas Darma Agung, 2020)
This study aims at finding the effect of job leadership, motivation and incentives on job satisfaction of BPKPAD employees in Binjai City. This research design uses quantitative descriptive. The sampling technique uses a saturated sampling method so that the sample is as many as 40 respondents. The independent variables in this study consist of job leadership (X1), motivation (X2), and incentives (X3), while the dependent variable is job satisfaction (Y). Data analysis was done by using multiple regression analysis. The results show that job leadership partially has a significant effect on employee job satisfaction at the Binjai Regional Financial, Revenue and Asset Management Agency with a t-count value of 2.894 > from t-table 1.685 or with a significance value of 0.006 < 0.05. Motivation partially has a significant effect on job satisfaction at BPKPAD Binjai City with a t-count value of 4.660 > from the t-table 1.685 or with a significance value of 0.000 < 0.05. Incentives partially have a significant effect on job satisfaction at BPKPAD Binjai City with a t-count value of 2.678 > from t-table 1.685 or with a significance value of 0.011 < 0.05. Work leadership, motivation and incentives simultaneously have a significant effect on incentives at the Binjai BPKPAD with an F-count value of 25.458 > F-table 2.87 or with a significance value of 0.000 < 0.05.